2001
DOI: 10.1111/j.1527-3466.2001.tb00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Eplerenone: A Selective Aldosterone Receptor Antagonist (SARA)

Abstract: Aldosterone, the final product of the renin-angiotensin-aldosterone system (RAAS), is a mineralocorticoid hormone that classically acts, via the mineralocorticoid (aldosterone) receptor, on epithelia of the kidneys, colon, and sweat glands to maintain electrolyte homeostasis. Aldosterone has also been shown to act at nonepithelial sites where it can contribute to cardiovascular disease such as hypertension, stroke, malignant nephrosclerosis, cardiac fibrosis, ventricular hypertrophy, and myocardial necrosis. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 53 publications
2
67
0
Order By: Relevance
“…Because aldosterone was recently shown to increase the abundance of the Na-Cl cotransporter (NCC) (17), an increase in NCC could be one potential compensatory change in response to the chronic blockade of AR that sustained Na ϩ reabsorption. A bolus dosage of epl given by oral gavage in rats was shown to reverse the effects of aldosterone on urinary Na ϩ /K ϩ ratio suggesting that AR antagonism is effective in acutely antagonizing the renal actions of aldosterone on electrolyte transport (6). Similarly, the present study identified an acute natriuresis associated with an initial period of negative renal Na ϩ balance at the onset of epl treatment.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…Because aldosterone was recently shown to increase the abundance of the Na-Cl cotransporter (NCC) (17), an increase in NCC could be one potential compensatory change in response to the chronic blockade of AR that sustained Na ϩ reabsorption. A bolus dosage of epl given by oral gavage in rats was shown to reverse the effects of aldosterone on urinary Na ϩ /K ϩ ratio suggesting that AR antagonism is effective in acutely antagonizing the renal actions of aldosterone on electrolyte transport (6). Similarly, the present study identified an acute natriuresis associated with an initial period of negative renal Na ϩ balance at the onset of epl treatment.…”
Section: Discussionsupporting
confidence: 51%
“…Inappropriately elevated circulating aldosterone concentrations may induce a number of pathophysiological consequences including sodium retention, hypertension, and fibrosis. Mineralocorticoid receptor (MR) antagonism has been shown to ameliorate cardiovascular and renal injury in several hypertensive models (6,7,19,26). Chronic MR antagonism should in theory increase urinary Na ϩ excretion and thus reduce blood pressure; however, in previous studies chronic treatment with MR antagonists did not acutely (23) nor chronically (10,21,23) alter urinary Na ϩ excretion suggesting that alternative renal mechanisms are invoked to compensate for the chronic blockade of the MR.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…In G3, the rats received 100 mg/kg/day of SAB starting from week 12 by gavage. The dose of SAB in the current study was almost comparable to that used in clinical practice (26). The animals were allowed free access to food and water throughout the acclimation and experimental protocols.…”
Section: Animals and Reagentsmentioning
confidence: 95%